A concept analysis of cultural competence - Cai, Duan-Ying (International journal of nursing sciences, 2016)
To clarify the meaning and reduce ambiguities of the concept cultural competence, and promote consistency in using the concept in nursing dialog, research, and practice. Using Walker and Avant's method of concept analysis. Cultural competence is the gradually developed capacity of nurses to provide safe and quality healthcare to clients of different cultural backgrounds. Its defining attributes are cultural awareness, cultural sensitivity, cultural knowledge, cultural skill, and dynamic process. Antecedents are cultural diversity, cultural encounter, and cultural desire. Consequences involve three beneficiaries, as follows: clients, nurses, and healthcare organizations. Empirical referents are primarily consisted in self-reported tools. The understanding of cultural competence of nurses that emerged in this concept analysis will contribute to the development of a rigorous design of instruments or research.